2021
DOI: 10.1039/d1dt01322j
|View full text |Cite|
|
Sign up to set email alerts
|

Novel cationic 1,2,4-selenadiazoles: synthesis via addition of 2-pyridylselenyl halides to unactivated nitriles, structures and four-center Se⋯N contacts

Abstract: 2-Pyridylselenyl halides undergo facile coupling with a triple CN bond of unactivated nitriles. Unprecedented heterocyclization allowed the preparation of novel class of cationic 1,2,4-selenadiazoles in remarkably high yields. Cationic 1,2,4-selenadiazoles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 17 publications
4
33
0
Order By: Relevance
“…The structural analysis revealed that dicationic 1,2,4-selenadiazoles in 7 formed [Se–Cl] 2 squares ( Figure 7 ), which we observed earlier [ 22 ]. It should be noted that the second chloride did not participate in ChB ( Figure 7 ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The structural analysis revealed that dicationic 1,2,4-selenadiazoles in 7 formed [Se–Cl] 2 squares ( Figure 7 ), which we observed earlier [ 22 ]. It should be noted that the second chloride did not participate in ChB ( Figure 7 ).…”
Section: Resultssupporting
confidence: 75%
“…), zero or very close to zero energy density (0.000–0.002 a.u.) in these bond critical points (3, –1), and estimated strength for appropriate short contacts (0.9–5.0 kcal/mol) are typical for weak hydrogen bonds [ 3 , 4 , 36 ] and non-covalent interactions involving halogen [ 8 , 9 , 10 , 11 , 12 , 32 , 37 , 38 ] and chalcogen [ 22 , 23 , 39 , 40 , 41 , 42 ] atoms in similar chemical systems. The strongest non-covalent interactions in the studied model supramolecular associates 3 – 10 were chalcogen bonds: Se1···Cl24 in 3 (4.7 kcal/mol), Se1···Cl30 in 4 (4.4 kcal/mol), Se1···Cl38 in 5 (5.0 kcal/mol), Se1···Cl24 in 6 (3.5 kcal/mol), Se29···Cl56 in 7 (5.0 kcal/mol), Se1···Br15 in 8 (3.5 kcal/mol), Se2···C31 in 9 (1.3 kcal/mol), and Se1···F29 (4.7 kcal/mol) in 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently showcased that the addition of 2-pyridylselenenyl halides to a triple CN bond of unactivated nitriles resulted in the formation of novel cationic 1,2,4-selenadiazoles [11]. Moreover, we showed that the Se atom in the adducts of 2-pyridylselenenyl halides and nitriles could provide two σ-holes and act as a donor ChB (Figure 1).…”
Section: Introductionmentioning
confidence: 91%
“…Following our interest in CN triple bond activation [1][2][3][4][5][6][7][8][9], here we report the synthesis of dirhodium tetraacetate di(cyclohexylisocyanide) [Rh 2 (O 2 CCH 3 ) 4 (C≡NCy) 2 ] (1) and the evaluation of the Rh(II) ability to activate isocyanides towards nucleophilic addition.…”
Section: Introductionmentioning
confidence: 99%